Studies of Sn Substitution on Ca and Cu Sites of Bi-Sr-Ca-Cu-O Superconducting System - Hashim, Azhan; Shaari, Abdul Halim; S. B., Mohamed; K., Azman; Syed Yahya, Syed Yusainee; Abd. Aziz, Sidek (Universiti Putra Malaysia Press, 2002)
The influence of Sn substitution on Ca and Cu sites in Bi-Sr-Ca-Cu-O superconductor system simultaneously or separately have been studied using xray diffraction (XRD) method and resistance measurement technique for the structural identification and determination of critical temperature, Tc respectively. Generally, all samples displayed a normal metallic behavior above TConse,' The values of TC(R'() decreased towards Sn concentration. However, the TC(R'() value for x=0.02 sample doped simultaneously in Ca and Cu sites was observed at 104 K The critical temperature increased by 4 K compared to that of the pure sample. Sample doped with Sn, for concentration of x=0.20, at Ca site or at both Ca and Cu sites show the dominance of the 2212 and 2201 phases. Hence, altering the Ca environment favours the formation of the low Tc phases. This observation was also supported by the information obtained from the XRD patterns. ew unidentified peaks (probably impurities) and low phase peaks corresponding to 2201 phase existed for samples with Sn concentration above x=0.15. No peaks belonging to Sn02 were detected implying that Sn probably has been incorporated into the crystalline structures of the BSCCO system or formed as impurities.